2003
DOI: 10.1046/j.1528-1157.2003.14003.x
|View full text |Cite
|
Sign up to set email alerts
|

Furosemide Terminates Limbic Status Epilepticus in Freely Moving Rats

Abstract: Summary:Purpose: To evaluate the anticonvulsant properties of furosemide and to determine sedative side effects compared with pentobarbital and diuretic side effects compared with saline-treated controls in an experimental model of limbic status epilepticus.Methods: Self-sustaining status epilepticus was induced in rats by continuous electrical stimulation of the perforant path. Five minutes after the end of the stimulation, animals were given 100 mg/kg furosemide, 30 mg/kg pentobarbital, or an equal amount of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 25 publications
(40 reference statements)
0
8
0
1
Order By: Relevance
“…We believe that differences in the models used, animal ages, treatment protocols, and doses of furosemide could be confounding factors. For example, Holtkamp et al reported that furosemide at 100 mg/kg terminates limbic SE elicited by continuous electric stimulation in freely moving rats, but the drug was delivered 2 hrs after SE and took 60–90 min to show an effect (Holtkamp et al, 2003). This is different from our experimental procedure in which we treated rats with furosemide 15 min before induction of seizures by pilocarpine.…”
Section: Discussionmentioning
confidence: 99%
“…We believe that differences in the models used, animal ages, treatment protocols, and doses of furosemide could be confounding factors. For example, Holtkamp et al reported that furosemide at 100 mg/kg terminates limbic SE elicited by continuous electric stimulation in freely moving rats, but the drug was delivered 2 hrs after SE and took 60–90 min to show an effect (Holtkamp et al, 2003). This is different from our experimental procedure in which we treated rats with furosemide 15 min before induction of seizures by pilocarpine.…”
Section: Discussionmentioning
confidence: 99%
“…[19,20] For FcRn binding measurement, 5×10 5 yeast cells were harvested, washed by PBSA (PBS + 0.1% bovine serum albumin) (pH 6.0) and re-suspended in 50 µL PBSA (pH 6.0) containing 100 nM biotin-conjugated soluble human FcRn (shFcRn). [21] The samples was kept on ice for 2 hrs, then the cells were washed by PBSA (pH 6.0) again and still re-suspended in 50 µL PBSA (pH 6.0). 1 µL PE-streptavidin (Invitrogen) was added into the re-suspended cells.…”
Section: Methodsmentioning
confidence: 99%
“…The results presented in this study reveal a functional link between CA activity and KCC2 in CA1 pyramidal neurons that may provide a significant contribution to the [K + ] o transients that are characteristic during epileptiform activity (Yaari et al 1986; Fröhlich et al 2008). Hence, it is possible that inhibition of the mechanism studied in this work is involved in the anti‐epileptic actions of furosemide (Hochman et al 1995; Gutschmidt et al 1999; Holtkamp et al 2003) and of carbonic anhydrase inhibitors (Thiry et al 2007).…”
Section: Introductionmentioning
confidence: 99%